2018
DOI: 10.1097/id.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Osstell Implant Stability Quotient and Penguin Resonance Frequency Analysis to Evaluate Implant Stability

Abstract: Osstell ISQ and Penguin RFA are reliable only when the implants are embedded in stiff materials. Osstell ISQ is more reliable than Penguin RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
2
21
0
2
Order By: Relevance
“…The current results are in accordance with those of Al-Jetaily et al (22) who investigated the sensitivity and reliability of the Osstell system compared to the Periotest system in implant bone simulated conditions (vitro study). The encountered results also agree with Gul Buyukguclu et al (23) who reported highly reliable of the Osstell system. In contrast to presented results, Bilhan et al (24) who reported that there was no significance when Periotest was compared with ISQ values observed for the same implants.…”
Section: Discussionsupporting
confidence: 91%
“…The current results are in accordance with those of Al-Jetaily et al (22) who investigated the sensitivity and reliability of the Osstell system compared to the Periotest system in implant bone simulated conditions (vitro study). The encountered results also agree with Gul Buyukguclu et al (23) who reported highly reliable of the Osstell system. In contrast to presented results, Bilhan et al (24) who reported that there was no significance when Periotest was compared with ISQ values observed for the same implants.…”
Section: Discussionsupporting
confidence: 91%
“…The measurements were taken immediately after implant placement in the vestibular and lingual positions perpendicular to SmartPeg rods (SmartPeg; Osstell AB, Gothenburg, Sweden), placed on the implants. The 22 implants' ISQ (Implant Stability Quotient) was measured at five stages: at baseline, and at 2, 6, 12, and 24 months after implant placement [28,29]. Sutures were removed two weeks after implant placement.…”
Section: Calibrationmentioning
confidence: 99%
“…Therefore, the RFA device relies on the physical phenomenon of resonance to determine the natural frequency of vibration of each implant and thus provide the clinician an implant stability quotient value (ISQ) on a scale of 0 to 100 (30). Currently, there are several devices on the market that use RFA as a method of measuring implant stability, such as the Osstell IDX (Osstell, Gothembourg, Sweden) and the Penguin RFA (Integration Diagnostics Sweden AB, Gothenburg, Sweden) (31,32). The objective of the present in vitro experimental study was to determine the influence of the presence of cortical bone and how the design of the implant impacts implant stability, as well as to compare the results of the measurements obtained using two different RFA devices.…”
Section: Introductionmentioning
confidence: 99%